Design and characterization of G-quadruplex RNA aptamers reveal RNA-binding by KDM5 lysine demethylases - Johanna Luige; Thomas Conrad; Alexandros Armaos; Annita Louloupi; Anna Vincent; David Meierhofer; Michael Gajhede; Gian Gaetano Tartaglia; Ulf Andersson Vang Ørom (Computational and Structural Biotechnology Journal)
Here, we show that the histone lysine demethylases KDM5A and KDM5B can bind to RNA through interaction with G-quadruplexes, despite neither being categorized as RNA- nor G-quadruplex binding proteins across numerous experimental large-scale and computational studies. In addition to characterizing the KDM5 G-quadruplex interaction we show that RNA is directly involved in the formation of KDM5-containing protein complexes. Computational predictions and comparisons to other ARID domain containing proteins suggest that the ARID domain is directly interacting with both DNA and RNA across several proteins. Our work highlights that the RNA-binding by KDM5 lysine demethylases is dependent on recognizing G-quadruplex structures and that RNA mediates the formation of alternative KDM5-containing protein complexes.